1998
DOI: 10.1021/ma9801669
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Dynamics in Dendrimers with Perfluorinated End Groups:  A Study Using Quasielastic Neutron Scattering

Abstract: A series of carbosilane dendrimer generations, GxRF6 (x = 1−3) with perfluorohexyl (−C6F13) groups on the surface and one dendrimer G3 without these end groups, have been studied using X-ray scattering and quasielastic neutron scattering. The GxRF6 form generation dependent superstructures as a result of the microphase separation between the end groups and the carbosilane core. The helical end groups tend to arrange in layers between the carbosilane domains. The dynamic structure factor was measured with two b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 24 publications
5
40
0
Order By: Relevance
“…For instance, Percec et al reported the observation of unexpected columnar supramolecular morphologies for perfluorocarbon-functionalized dendrimers, produced by assembly processes that were driven by a fluorophobic effect, in contrast to spherical dendrimer assemblies that were characterized for perhydrogenated analogs. [1,2] The inclusion of fluorocarbons within the structures of phenylene, [3] carbosilane, [4,5] benzyl ether, [6] and phosphorus-containing dendrimers [7] has also been utilized to modify their respective physical properties. [8] Many examples of fluorocarbon-containing hyperbranched polymers have been reported, for which the fluorocarbon content is either the intentional or unintentional result of the chemistry employed for polymerization [9][10][11][12][13][14][15][16][17][18] or is introduced through subsequent chemical modification.…”
Section: Feature Articlementioning
confidence: 99%
“…For instance, Percec et al reported the observation of unexpected columnar supramolecular morphologies for perfluorocarbon-functionalized dendrimers, produced by assembly processes that were driven by a fluorophobic effect, in contrast to spherical dendrimer assemblies that were characterized for perhydrogenated analogs. [1,2] The inclusion of fluorocarbons within the structures of phenylene, [3] carbosilane, [4,5] benzyl ether, [6] and phosphorus-containing dendrimers [7] has also been utilized to modify their respective physical properties. [8] Many examples of fluorocarbon-containing hyperbranched polymers have been reported, for which the fluorocarbon content is either the intentional or unintentional result of the chemistry employed for polymerization [9][10][11][12][13][14][15][16][17][18] or is introduced through subsequent chemical modification.…”
Section: Feature Articlementioning
confidence: 99%
“…Keywords Dendrimers AE Hydrodynamic properties AE Volume of end groups X-ray scattering [10,19,20], light scattering [21,22], and by size-exclusion chromatography [21,[23][24][25][26]. In several works the hydrodynamic properties of dendrimer molecules were measured by different techniques [9,16,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Molecular Characteristics Of Poly(propylene Imine) Dendrimermentioning
confidence: 99%
“…Reports studying the molecular properties of dendrimers by different physical techniques are not numerous enough. In general, dendrimer molecules were studied by neutron scattering [9][10][11][12][13][14][15][16][17][18],…”
Section: Introductionmentioning
confidence: 99%
“…NMR [46,51,59,60], neutron scattering [61][62][63], dielectric relaxation spectroscopy [64,65], rheology [66], fluorescence anisotropy [67], and molecular and Brownian dynamics computation [68][69][70][71] have provided some information about the mobility of the different segments constituting a dendrimer, generally via the rotational correlation time (τ C ) of the segments. The overall conclusion of these studies is that the chain ends are more mobile than the internal segments, and that their rotational correlation time is not much affected by increasing G values.…”
Section: Introductionmentioning
confidence: 99%